UPAYA PEMERINTAH DESA DALAM MENINGKATKAN KUALITAS PELAYANAN PADA MASYARAKAT - PREDRIK KWAN; Willy Tri Hardiyanto; Dody Setyawan (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
Abstract: Abstraction This Base On Reality That which Indicate Still There are many Deficient in And Mistrust hello world In The government The village,Then Study Concerning The effort BecomeVery Relevant To Raised. The implication of The application Service The area also Sue The village DoVarious Multiform Renewal InInternally AsWas prosecuted By Services.The renewal of this Just possible Done Manakalah The government The village Already Capable of being Empowering Her.To depart From thinking The thenViewed Need Do Study hello word The government hello word To Good Service On People.Formulating The problem In Research It is How Conditions The The villagers Lismanggu Viewed from Conditions Three Or actor Acolonnade Government Existing.And what is the Berdayaan of The The government Villages District Prafi A county Manokwari And post-conflict -upaya what Should Done in The implementation of the village.An inference It is obtainable In order to Upayan government Divided into the three concepts Governments and government The village, a body of s consultative The village, civil society Village and sub-district prafi while.The effort That is over This Made to empower Or improve Capacity The government has yet to Optimal and have not shown The act of one who Sistematiik( still half-hearted and partial )And Concentrated On the fields A particular.Our suggest ions The ask is The village was, okay Who muflak to Done.An effort made By integrating Various needs,Every actor And the approach A systemic.The Government Regency expected more focus attention Organization of theT he village Government efforts throughthe granting of the aid in the form of the allocation offunds for implementation of the Government's efforts of village Lismanggu district prafi district of Manokwari.